Carotenoids and retinal disease - Landrum, John T, Ed; Nolan, John M, Ed (CRC Press, 2014)
"This book outlines the pathological conditions of the central retina where the macular pigment is known to have its greatest involvement in protection against photooxidative damage. The book focuses on the nature of the macular carotenoids, their transport and accumulation within the retina, and their influence on the etiology of retinal diseases. It also includes chapters that provide readers an understanding of the epidemiology and pathology of these diseases and the known factors which contribute to them"--Provided by publisher.